Obstructive sleep apnea in outpatient anesthesia practice (a literature review) - D.A. Krishtafor; O.M. Klygunenko; D.M. Stanin (Медицина неотложных состояний, 2022)
Obstructive sleep apnea is a common and often overlooked condition. Its main manifestation is the pause of spontaneous breathing during sleep with a frequency of more than five times per hour with awakenings, sleep disturbances and, as a result, daytime sleepiness. Obstructive sleep apnea is most commonly associated with obesity. It is recognized that there is a link between this disease and hypertension, coronary heart disease, and strokes. Diagnosis requires special research methods such as polysomnography. There are fairly simple questionnaires that allow suspecting this condition (Epworth scale, STOPBang questionnaire). In outpatient surgery, obstructive sleep apnea syndrome (in combination with obesity) is dangerous due to difficult airways, the risk of apnea upon recovery from anesthesia, sudden death in the postoperative period. This review presents methods of correction of this condition, features of the preoperative assessment of patients, intraoperative management, and features of awakening in the post-anesthetic period.